2010
DOI: 10.3171/2010.4.peds1014
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of brain and cerebrospinal fluid growth in normal versus hydrocephalic mice

Abstract: Object Hydrocephalus has traditionally been quantified by linear measures of ventricular size, with adjunct use of cortical mantle thickness. However, clinical outcome depends on cognitive function, which is more directly related to brain volume than these previous measures. The authors sought to quantify the dynamics of brain and ventricular volume growth in normal compared with hydrocephalic mice. Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…To make some progress in understanding how inflammation could contribute to the onset and evolution of hydrocephalus using our model, we used brain volumetric data for healthy and untreated hydrocephalic mice published in [3]. For simplicity we took λ 2mα = 1 in Eq.…”
Section: Application To Hydrocephalusmentioning
confidence: 99%
See 1 more Smart Citation
“…To make some progress in understanding how inflammation could contribute to the onset and evolution of hydrocephalus using our model, we used brain volumetric data for healthy and untreated hydrocephalic mice published in [3]. For simplicity we took λ 2mα = 1 in Eq.…”
Section: Application To Hydrocephalusmentioning
confidence: 99%
“…In this chapter, we propose a mathematical model using Hamilton's principle that captures some of the brain's dynamics during the evolution of hydrocephalus. We define current healthy healing and abnormal inflammation states and investigate the relationship between these states using volumetric data of healthy and untreated hydrocephalic mice reported in [3].…”
Section: Introductionmentioning
confidence: 99%
“…ydrocepHalus is accompanied by pathological changes in brain morphology, including thinning of the cortex, increases in water content, and loss of myelin in the periventricular white matter. 2,3,7,10,11,14 However, treatment and evaluation remain focused on normalizing CSF volume, while measures of brain volume are not generally available. In a mouse model of hydrocephalus, we have previously shown that valuable information relevant to hydrocephalus can be obtained by measuring brain volume in addition to estimates of fluid aBBreViatiONS BSID = Bayley Scales of Infant and Toddler Development, third edition; CPC = choroid plexus cauterization; ETV = endoscopic third ventriculostomy; FOHR = frontal-occipital horn ratio; LDA = linear discrimination analysis; VP = ventriculoperitoneal.…”
mentioning
confidence: 99%
“…2,3,7,10,11,14 However, treatment and evaluation remain focused on normalizing CSF volume, while measures of brain volume are not generally available. In a mouse model of hydrocephalus, we have previously shown that valuable information relevant to hydrocephalus can be obtained by volume and head circumference.…”
mentioning
confidence: 99%
See 1 more Smart Citation